Performa Media, Jurnalisme Empati, dan Jurnalisme Bencana: Kinerja Televisi Indonesia dalam Peliputan Bencana (Kasus Liputan TV One terhadap Hilangnya Air Asia QZ 8501): Kinerja Televisi Indonesia dalam Peliputan Bencana - Ignatius Haryanto (Universitas Multimedia Nusantara, 2016)
This research aims to present an analysis toward TV One as one of Indonesian television stations, whether it works in line with the concept McQuail's media performance and the concept of empathy journalism coined by Ashadi Siregar. TV One coverage on the missing Air Asia QZ 8501 is purposively selected to be analysed using case study method. The data collected is analyzed based on disaster journalism perspective and ethical guide on Broadcasting Code of Conduct and Program Standards (P3SPS). The missing Air Asia QZ 8501 at the end of December 2014 shows TV One prioritized speed and sensationalism in delivering the story, rather than considering on the kind of news that ideally received by the audience. This articles highlights the way TV One covered the Air Asia tragedy, mainly on its breaking news which reported the finding of floating dead bodies on the ocean few days after the accident.